Achieving highly practical capacitance of MnO2 by using chain-like CoB alloy as support. Issue 16 (17th April 2018) - Yan, Jingjing; Wang, Hui; Ji, Shan; Pollet, Bruno G.; Wang, Rongfang
Abstract : A uniform coating of an MnO2 layer on the chain-like CoB surface was formed to improve the cycling stability. Abstract : The practical performance of MnO2 as a capacitor material is limited mainly by its poor electronic conductivity. Arranging MnO2 on the conductive backbone to form a unique hierarchical nanostructure is an efficient way to enhance its capacitor performance. Herein, a hierarchically core–shell structure, in which thin γ-MnO2 sheets are grown on amorphous CoB alloy nano-chains (CoB@MnO2 ), is produced via a simple and scalable solution-phase procedure at room temperature. A specific capacitance of 612.0 F g −1 is obtained for the CoB@MnO2 capacitor electrode at a discharge current density of 0.5 A g −1, a value higher than those obtained for other conductive materials supported MnO2 electrodes reported in the literature. A rate retention value of 60.9% of its initial capacitance is obtained when the discharge current density increased by 12-fold. It is found that after 6000 charge–discharge cycles at 2 A g −1, the specific performance of CoB@MnO2 is 86.5%. The excellent capacitor performance of CoB@MnO2 is explained to be due to the hierarchical core–shell structure, in which the CoB alloy nano-chain backbone provides a transport pathway for the electron, and the porous MnO2 outer layers provide the channel for mass transfer, hence allowing further exposure to active sites. The combination of high capacitor performance and low-cost synthesis makes the core–shell CoB@MnO2 a promising cathode material for alkaline electrolyte supercapacitors.